Avstrijska slovenistika in slovenska literarna veda - Leben, Andrej (Primerjalna književnost, 2012)
This article discusses the development of Slovenian studies in Austria after 1918 with a special emphasis on current literary studies and its contribution to the discourse of scholarship on Slovenian literary studies. The first part focuses on the structural, staffing, and content-related dimensions of the discipline, and the second part outlines the literary studies focal points with which the research in Slovenian studies in Austria occupies a special place within Slovenian literary studies.
Keywords: avstrijska literarna veda; Slavic studies; slavistika; Slovene studies; slovenistika; slovenska literarna veda